2021
DOI: 10.1007/s43630-021-00051-9
|View full text |Cite
|
Sign up to set email alerts
|

Low-power infrared laser modulates telomere length in heart tissue from an experimental model of acute lung injury

Abstract: Acute lung injury and acute respiratory distress syndrome can occur as a result of sepsis. Cardiac dysfunction is a serious component of multi-organ failure caused by severe sepsis. Telomere shortening is related to several heart diseases. Telomeres are associated with the shelterin protein complex, which contributes to the maintenance of telomere length. Low-power infrared lasers modulate mRNA levels of shelterin complex genes. This study aimed to evaluate effects of a low-power infrared laser on mRNA relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Existing data suggest a close relationship between TL and inflammation and the immune system, indicating a potential connection between TL and sepsis. An animal experiment’s results have shown that after lipopolysaccharide (LPS)-induced acute lung injury (ALI), telomeres in rat heart tissue exhibited shortening, suggesting that sepsis may affect TL in the chromosomes of the animal’s heart 10 . Recent research assessed variations in leukocyte telomere length (LTL) during 7 days in 40 critically sick patients, finding that LTL shortened in 21 patients, lengthened in 11, and remained unchanged in the rest of the patients.…”
Section: Introductionmentioning
confidence: 99%
“…Existing data suggest a close relationship between TL and inflammation and the immune system, indicating a potential connection between TL and sepsis. An animal experiment’s results have shown that after lipopolysaccharide (LPS)-induced acute lung injury (ALI), telomeres in rat heart tissue exhibited shortening, suggesting that sepsis may affect TL in the chromosomes of the animal’s heart 10 . Recent research assessed variations in leukocyte telomere length (LTL) during 7 days in 40 critically sick patients, finding that LTL shortened in 21 patients, lengthened in 11, and remained unchanged in the rest of the patients.…”
Section: Introductionmentioning
confidence: 99%